PELATIHAN DAN PENGUATAN KAPASITAS MAHASISWA DALAM INOVASI MEDIA DAN METODE PEMBELAJARAN SD DI ERA KURIKULUM MERDEKA - Mariyani, Anna; Arrosyad, Muhammad Iqbal; Astuti, Aprilia Dwi (Abdi Masya, 2025)
This activity was conducted to evaluate the effectiveness of training in enhancing student skills, particularly in media innovation and learning methods, during the Merdeka Curriculum era. The primary issue arising from the implementation of the Merdeka Curriculum is the need for educators to be more creative in developing teaching modules, learning flows, and learning objectives, ensuring that lesson plans are prepared thoughtfully and effectively. This community service program is designed for 350 students in the Elementary School Teacher Education Undergraduate Program at Muhammadiyah University of Bangka Belitung, aiming to enhance their knowledge and capacity in designing innovative learning experiences at the elementary school level. The training method is conducted through three stages: preparation, implementation, and evaluation. The results of the community service have shown that the training has a significant impact on improving the skills of participants in each observation semester. In Semester 2, skills increased from 50 to 80 (60%); in Semester 4, from 40 to 85 (112.5%); in Semester 6, from 30 to 90 (200%); and in Semester 8, from 45 to 88 (95.6%). The most significant improvement occurred among participants with low initial abilities, demonstrating the significant benefits this group gained from the training. Overall, the training proved effective in improving students' cognitive abilities, as evidenced by the pretest and posttest results. These findings demonstrate that the community service program consistently has a positive impact on preparing students to meet the demands of learning innovation under the Independent Curriculum.